GROWTH PROMOTION OF Schizolobium parahyba var. amazonicum SEEDLINGS USING STRAINS OF Trichoderma spp. UNDER PHOSPHORUS RATES - de Oliveira, Luís Augusto Batista; Pereira Resende, Cecília Leão; Cintra, Pedro Henrique Nascimento; Costa Carvalho, Daniel Diego; Rodrigues, Fabricio (Floresta, 2023)
Fungi of the genus Trichoderma are significantly important for promoting the growth of different plant species. Moreover, they have been connected to high nutrient absorption. Thus, the objective of this study was to evaluate the initial development of seedlings of Brazilian firetree [Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby] with application of Trichoderma spp. and phosphorus (P) rates. A randomized block design with seven replications was used, in a 4×5 factorial arrangement (strains and P rates); the P rates were applied using 0, 64, 128, 192, and 256 mg dm-3 of P2O5 (triple superphosphate). The characteristics evaluated were plant height (PH), stem diameter (SD), leaf fresh weight (LFW), leaf dry weight (LDW), stem fresh weight (SFW), stem dry weight (SDW), shoot fresh weight (SHFW), and shoot dry weight (SHDW). The results showed that Trichoderma spp. promotes satisfactory conditions for growing Schizolobium parahyba var. amazonicum, and the strain Trichoderma harzianum IBLF 006 WP at P2O5 rate of approximately 128 mg dm-3provided the highest increase in the evaluated variables.